EFEKTIVITAS PENGGUNAAN EKSTRAK ANTOSIANIN TANAMAN BUNGA KEMBANG SEPATU UNTUK MENDETEKSI BORAKS PADA BAKSO - Rio Purnama (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2021)
One of the causes of food safety problems in Indonesia is the lack of knowledge, responsibility and supervision by producers, consumers and the authorities. This results in cheating by irresponsible food producers, adding ingredients that can harm the human body. There are several ways to detect or detect the presence of hazardous food additives, one of which is using indicators made from natural ingredients added with several other ingredients that can detect hazardous food additives, one of which is borax. After conducting research on the effectiveness of hibiscus flower anthocyanin extract as an indicator of borax detection in meatballs, it was found that hibiscus flower extract can be used as an indicator for borax detection, seen from the change in the color of hibiscus flower extract which at first is brownish orange (purplish. ) After being absorbed with meatballs containing borax, the hibiscus flower extract changes its color to dark brown red, this is due to the pelagornidin antasianin compounds reacting with borax compounds.